Industrial Separation Processes : Fundamentals - Haan, André B. de; Eral, H. Burak; Schuur, Boelo (De Gruyter Textbook, 2020)
Separation processes on an industrial scale account for well over half of the capital and operating costs in the chemical industry. Knowledge of these processes is key for every student of chemical or process engineering. This book is ideally suited to university teaching, thanks to its wealth of exercises and solutions. The second edition boasts an even greater number of applied examples and case studies as well as references for further reading.